Comparison of Plasma Viscosity Following Administration of Albumin 5% in Half-Normal Saline versus Normal Saline during Minor Surgeries - Atabak Najafi; Mozhde Jalali; Farhad Etezadi; Mohammad Reza Khajavi; Reza Shariat Moharari; Farsad Imani; Peiman Pourfakhr; Mojtaba Mojtahedzadeh (Archives of Anesthesia and Critical Care, 2015)
Background: We aimed to compare the effect of albumin 5% in half normal saline (half NS) versus normal saline (NS) infusion on the plasma viscosity in the near-normal physiological condition. According to the high oncotic pressure of albumin along with prolonged half-life of its molecules in comparison to NS in the intra-vascular compartment, it has been proposed that a more significant reduction of the plasma viscosity might be expected after the infusion of albumin. Methods: A total of 56 patients referring to the general operating room for their elective minor surgeries were evenly divided into two groups (V1, V2). It was calculated that 28 patients were needed to be enroll in each study group to detect a difference as big as 0.15 millipoise (mPa.s) with a statistical power of 80%.  The V1 group received 1000 ml of NS but the V2 group received 1000 ml of recombinant albumin 5% in half NS within one hour, as fluid replacement therapy, during the intra-operative period. We have designed a simple measurement system according to Poiseuille’s formula by which the viscosity value could be measured reliably since the system was calibrated frequently using distilled water as a reference. Results: The mean value of the pre-operative plasma viscosity of the patients was 1. 73 ± 0.25 mPa.s and 1.76 ± 0.21 mPa.s in V1 and V2 groups respectively. After the infusion of the fluids, the mean viscosity values decreased to 1. 68 ± 0.30 mPa.s and 1.66 ± 0.17mPa.s in V1 and V2 groups respectively (p= 0.37).